IDENTIFIKASI MIKROBIOLOGI (STAPHYLOCOCCUS DAN COLIFORM) PADA SUSU DAN DAGING SERTA OLAHANNYA DI KOTA JOGJAKARTA - Ni Sri Yuliani; Aven B. Oematan (Partner, 2013)
Microbiology Identification (Staphylococcus and Coliform) of Milk, Meat and Their Processed Products in Jogjakarta City. Food is a perishable foods by microorganisms that can be harmful to consumers' health. Staphylococci and coliform commonly found in foods. The objective of this study was to know the type of contaminants in samples of meat and milk and processed products and growth in culture media. Materials examined were dairy and meat and dairy that come from the city of Jogjakarta. This study was conducted in August 2010 at the Laboratory of Veterinary Public Health Faculty, Gadjah Mada University. The method used in the microbiological examination is the method of casting and counting the cup.The results obtained from both methods of inspection showed there Staphylococcus and coliform contaminants in the material examined. The number of bacteria Staphylococcus sp on Vogel-Johnson media showed a high coliform in fresh milk while Violet Red Bile media found in raw milk and raw chicken meat. The results obtained in excess of standards established SNI No. 01-7388-2009. Obtained from the examination can be concluded that the number of bacteria exceeds SNI standards are set. Reklama: Bendradarbiaujame su stambiausiai Lietuvos ir užsienio automobiliu daliu tiekejais bei gamintojai todel auto detales galime pasiulyti geromis kainomis UAB ŠIAULIU AUTODOTA Keywords: Staphylococcus, Coliform, Milk, Meat